Mathematical modelling of an ejector refrigeration system - N Satheesh Kumar (2012)
The purpose of this project is to examine the working principals of an ejector refrigeration cycle and develop a mathematical model of the ejector refrigeration system. The vapour ejector is the vital component affecting the performance of the ejector refrigeration cycle. Therefore two distinct models have been formulated such that the ejector can either be studied independently or as a part of the entire refrigeration cycle.